Effects of seizure burden on structural global brain networks in patients with unilateral hippocampal sclerosis. Issue 8 (9th June 2021) - Corrêa, Diogo Goulart; Tijms, Betty M.; Dicks, Ellen; Rêgo, Cláudia; Alves‐Leon, Soniza Vieira; Marcondes, Jorge; Gasparetto, Emerson Leandro; van Duinkerken, Eelco
Abstract: Background and purpose: Temporal lobe epilepsy secondary to hippocampal sclerosis is related to epileptogenic networks rather than a focal epileptogenic source. Graph‐theoretical gray and white matter networks may help to identify alterations within these epileptogenic networks. Methods: Twenty‐seven patients with hippocampal sclerosis and 14 controls underwent magnetic resonance imaging, including 3D‐T1, fluid‐attenuated inversion recovery, and diffusion tensor imaging. Subject‐specific structural gray and white matter network properties (normalized path length, clustering, and small‐worldness) were reconstructed. Group differences and differences between those with higher and lower seizure burden (<4 vs. ≥4 average monthly seizures in the last year) in network parameters were evaluated. Additionally, correlations between network properties and disease‐related variables were calculated. Results: All patients with hippocampal sclerosis as one group did not have altered gray or white matter network properties (all p  > .05). Patients with lower seizure burden had significantly lower gray matter small‐worldness and normalized clustering compared to controls and those with higher seizure burden (all p  < .04). A higher number of monthly seizures was significantly associated with increased gray and white matter small‐worldness, indicating a more rigid network. Conclusion: Overall, there were no differences in network properties in this group of patients with hippocampal sclerosis. However, patients with lower seizure burden had significantly lower gray matter network indices, indicating a more random organization. The correlation between higher monthly seizures and a more rigid network is driven by those with higher seizure burden, who presented a more rigid network compared to those with a lower seizure burden. Abstract : Temporal lobe epilepsy secondary to hippocampal sclerosis is related to abnormal epileptogenic networks, including multiple temporal and extra‐temporal structures, rather than a single focal epileptogenic source. This study aims to assess alterations within structural gray and white matter networks in patients with hippocampal sclerosis, through a graph theory analysis. In patients with hippocampal sclerosis, a more rigidly organized network (higher small‐worldness) was related to having more monthly seizures; also, patients with low seizure burden had significantly lower gray matter small‐worldness and normalized clustering compared to controls and those with high seizure burden.